Weeds biodiversity and maize growth in agro-pastoral integration system - Zhang Yuyang; Wang Junfeng; Sha Zhipeng; Guan Fachun; Duan Jing (浙江大学学报. 农业与生命科学版, 2014)
Weeds have direct impact on crop quality and yield in agricultural systems. Reasonable weed management should protect or improve the biodiversity of farmland weed communities for a better ecological environment with not only increasing crop yield, but also reducing use of herbicides.Based on the study of weeds community structure and the agronomic characters of maize in the two production patterns, i. e., “agro-pastoral integration”(hereinafter referred to as API) and conventional maize planting (hereinafter referred to as CK), this paper analyzed the differences of weed species, their functional groups and biodiversity indices before and after grazing. Comparison of maize growth in the two treatments was also drawn in this paper.It was shown that before grazing there were 17 different kinds of weeds in API and 12 in CK, and the total weed density in API was 2.20 times as much as that in CK, showing a significant difference (P<0.05). It was also noted that in API, the abundance distribution of the dominant weed was considerably large. However, after grazing the weed in API and CK reduced by 4 and 6 species and the total weed density of API was 3.44 times as much as that of CK, showing a significant difference (P<0.05) between the two treatments. From the perspective of functional group, both of the treatments were dominated by dicotyledonous angiosperm and annual and biennial (DA) and its abundance further increased after grazing. With regard to productivity of weed community, the biomass in API was 5.42 times as much as that in CK before grazing and 4.79 times after grazing, showing a highly significant difference (P<0.01). In terms of diversity, before grazing the Shannon-Wiener, Margalef and Simpson diversity indices in API were respectively 1.15, 1.25 and 1.08 times as much as those in CK, but the Pielou evenness index was low. After grazing, however, those indexes in API were 1.29, 1.64 and 1.10 times as much as those in CK. Among them, the Shannon-Wiener and Margalef diversity indices between the two treatments were quite different (P<0.05); and the Pielou evenness index in CK was 1.10 times as much as that of API, showing a significant difference (P<0.05). The similarity index of weed community was 0.76 before grazing, and it decreased to 0.23 after grazing. As for the agronomic characteristics of maize, at its silking and maturity stages, the values of plant height, leaf length and width, ear height and stem diameter of maize in API were all higher, but its chlorophyll content in the leaf was low compared with CK. It was also noted that the leaf area in API decreased after grazing. With respect to its yield, though API resulted in a yield reduction of 6.22%, the loss, however, could be compensated or even overcompensated by the producing of geese.In conclusion, API is able to maintain higher weed diversity in the field and at the same time, has slightly impact on the yield of maize.